RIESGOS BIOLÓGICOS EN EL LABORATORIO DE BIOTECNOLOGÍA DEL CAMPUS LA MARÍA DE LA UNIVERSIDAD TÉCNICA ESTATAL DE QUEVEDO - MURILLO LEÓN, GEOVANNA MISHEL (2025)
The purpose of this work was to identify and analyze the biological risks present in the Biotechnology Laboratory of the La María Campus of the Quevedo State Technical University